A web-based self-management programme for people with type 2 diabetes: the HeLP-Diabetes research programme including RCT - Murray, E; Ross, J; Pal, K; Li, J; Dack, C; Stevenson, F; Sweeting, M; Parrott, S; Barnard, M; Yardley, L; Michie, S; May, C; et al. (National Institute for Health Research, 2018)
Background: In the UK, 6% of the UK population have diabetes mellitus, 90% of whom have type 2 diabetes mellitus (T2DM). Diabetes mellitus accounts for 10% of NHS expenditure (£14B annually). Good self-management may improve health outcomes. NHS policy is to refer all people with T2DM to structured education, on diagnosis, to improve their self-management skills, with annual reinforcement thereafter. However, uptake remains low (5.6% in 2014–15). Almost all structured education is group based, which may not suit people who work, who have family or other caring commitments or who simply do not like group-based formats. Moreover, patient needs vary with time and a single education session at diagnosis is unlikely to meet these evolving needs. A web-based programme may increase uptake. Objectives: Our aim was to develop, evaluate and implement a web-based self-management programme for people with T2DM at any stage of their illness journey, with the goal of improving access to, and uptake of, self-management support, thereby improving health outcomes in a cost-effective manner. Specific objectives were to (1) develop an evidence-based theoretically informed programme that was acceptable to patients and health-care professionals (HCPs) and that could be readily implemented within routine NHS care, (2) determine the clinical effectiveness and cost-effectiveness of the programme compared with usual care and (3) determine how best to integrate the programme into routine care. Design: There were five linked work packages (WPs). WP A determined patient requirements and WP B determined HCP requirements for the self-management programme. WP C developed and user-tested the Healthy Living for People with type 2 Diabetes (HeLP-Diabetes) programme. WP D was an individually randomised controlled trial in primary care with a health economic analysis. WP E used a mixed-methods and case-study design to study the potential for implementing the HeLP-Diabetes programme within routine NHS practice. Setting: English primary care. Participants: People with T2DM (WPs A, D and E) or HCPs caring for people with T2DM (WPs B, C and E). Intervention: The HeLP-Diabetes programme; an evidence-based theoretically informed web-based self-management programme for people with T2DM at all stages of their illness journey, developed using participatory design principles. Main outcome measures: WPs A and B provided data on user ‘wants and needs’, including factors that would improve the uptake and accessibility of the HeLP-Diabetes programme. The outcome for WP C was the HeLP-Diabetes programme itself. The trial (WP D) had two outcomes measures: glycated haemoglobin (HbA1c) level and diabetes mellitus-related distress, as measured with the Problem Areas in Diabetes (PAID) scale. The implementation outcomes (WP E) were the adoption and uptake at clinical commissioning group, general practice and patient levels and the identification of key barriers and facilitators. Results: Data from WPs A and B supported our holistic approach and addressed all areas of self-management (medical, emotional and role management). HCPs voiced concerns about linkage with the electronic medical records (EMRs) and supporting patients to use the programme. The HeLP-Diabetes programme was developed and user-tested in WP C. The trial (WP D) recruited to target (n = 374), achieved follow-up rates of over 80% and the intention-to-treat analysis showed that there was an additional improvement in HbA1c levels at 12 months in the intervention group [mean difference –0.24%, 95% confidence interval (CI) –0.44% to –0.049%]. There was no difference in overall PAID score levels (mean difference –1.5 points, 95% CI –3.9 to 0.9 points). The within-trial health economic analysis found that incremental costs were lower in the intervention group than in the control group (mean difference –£111, 95% CI –£384 to £136) and the quality-adjusted life-years (QALYs) were higher (mean difference 0.02 QALYs, 95% CI 0.000 to 0.044 QALYs), meaning that the HeLP-Diabetes programme group dominated the control group. In WP E, we found that the HeLP-Diabetes programme could be successfully implemented in primary care. General practices that supported people in registering for the HeLP-Diabetes programme had better uptake and registered patients from a wider demographic than those relying on patient self-registration. Some HCPs were reluctant to do this, as they did not see it as part of their professional role. Limitations: We were unable to link the HeLP-Diabetes programme with the EMRs or to determine the effects of the HeLP-Diabetes programme on users in the implementation study. Conclusions: The HeLP-Diabetes programme is an effective self-management support programme that is implementable in primary care. Future work: The HeLP-Diabetes research team will explore the following in future work: research to determine how to improve patient uptake of self-management support; develop and evaluate a structured digital educational pathway for newly diagnosed people; develop and evaluate a digital T2DM prevention programme; and the national implementation of the HeLP-Diabetes programme. Trial registration: Research Ethics Committee reference number 10/H0722/86 for WPs A–C; Research Ethics Committee reference number 12/LO/1571 and UK Clinical Research Network/National Institute for Health Research (NIHR) Portfolio 13563 for WP D; and Research Ethics Committee 13/EM/0033 for WP E. In addition, for WP D, the study was registered with the International Standard Randomised Controlled Trial Register as reference number ISRCTN02123133. Funding details: This project was funded by the NIHR Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 6, No. 5. See the NIHR Journals Library website for further project information.